BRANDING WISATA BERBASIS PEMASARAN DIGITAL DI DESA YEHEMBANG KANGIN, KABUPATEN JEMBRANA - Ni Putu Elvian Andreani (Jurnal Nawala Visual, 2023)
Yehembang Kangin tourism village is one of the tourism villages based on nature, man-made and religion with the main branding titled "Tri Hita Karana". Problems with promotion and branding concepts that are still immature cause the marketing process of tourist destinations to run slowly. This article presents the formulation of an appropriate digital-based marketing branding strategy as a first step in improving the image of tourism in Yehembang Kangin Tourism Village. The data in the form of interviews about tourism marketing conditions, observation data on field conditions, and visitor review survey data were processed using content analysis methods, gap analysis, and qualitative descriptive analysis. The result is a general strategy to strengthen the "Tri Hita Karana" branding, one of which is by increasing the structuring of the promotion concept and branding concept and improving the quality of the network to various digital platforms to build regional image.